2004
DOI: 10.1002/hbm.20014
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of GABA‐related signalling is associated with increase of functional connectivity in human cortex

Abstract: Structural or operational synchrony analysis with EEG was conducted in order to detect functional interaction between cortical areas during an enhanced inhibition induced by the GABAergic agonist lorazepam in a double-blind, randomized, placebo-controlled, cross-over study in eight healthy human subjects. Specifically, we investigated whether a neuronal inhibitory system in the brain mediates functional decoupling of cortical areas. Single-dose lorazepam administration resulted in a widespread increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
49
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 72 publications
11
49
0
1
Order By: Relevance
“…These results complement those reported in Alonso et al (2010) and Fingelkurts et al (2004). These significant increases could be related with a strengthening of locallevel neural interactions which have been modeled as chaotic in nature (Freeman 2003;Polunina and Davydov 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results complement those reported in Alonso et al (2010) and Fingelkurts et al (2004). These significant increases could be related with a strengthening of locallevel neural interactions which have been modeled as chaotic in nature (Freeman 2003;Polunina and Davydov 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Benzodiazepine effects on the EEG have been studied by means of several techniques such as classical spectral analysis (Tan et al 1998), coherence (Romano et al 2002;Sampaio et al 2007), structural synchrony (Fingelkurts et al 2004) and cross-mutual information (Alonso et al 2010). In this last study, interesting drug-related changes were obtained and they were not bounded to any specific region of the scalp.…”
Section: Discussionmentioning
confidence: 96%
“…Significant differences were also observed across moments, except in the delta band. In synthesis, the drug clearly promoted an enhancement of cortical interhemispheric coherence, which is in accordance with Fingelkurts et al 24 , who conducted possibly the most expressive work related to the effects of a benzodiazepine on interhemispheric coherence. These authors investigated whether lorazepam would generate a functional decoupling of cortical areas and concluded that, unexpectedly, the drug yielded a widespread increase in the inter-area functional connectivity.…”
Section: Discussionsupporting
confidence: 87%
“…In this sense, the results of the present study indicate that the cortical inhibition produced by this benzodiazepine may be an efficient mechanism. As stated by Fingelkurts et al 24 , despite the common belief that this pharmacological class impairs brain functioning by switching off irrelevant functional connections, it seems that benzodiazepine intake increases the strength of functional links and promotes functional coupling between different cortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…phMRI and evoked pain fMRI J Upadhyay et al from the disruption of GABA-and glutamate-mediated processes, which are heavily present in the sensorimotor and limbic system circuitry (Fingelkurts et al, 2004). As with the phMRI infusion responses, the modulation of functional connectivity due to BUP administration is likely to be a combination of pharmacological effects in regions with high densities of m-opioid receptors as well as downstream structures (see Supplementary information for study limitations).…”
Section: Measurement Of Phmri Infusion Responses and Pharmacological mentioning
confidence: 99%